Advances in directional and linear statistics a festschrift for Sreenivasa Rao Jammalamadaka - Wells, Martin (Martin T.); Sengupta, Ashis (Physica-Verlag, 2011)
The present volume consists of papers written by students, colleagues and collaborators of Sreenivasa Rao Jammalamadaka from various countries, and covers a variety of research topics which he enjoys and contributed immensely to.